Graphene oxide supported liposomes as red emissive theranostics for phototriggered tissue visualization and tumor regression - Prasad, Rajendra; Yadav, Amit S.; Gorain, Mahadeo; Chauhan, Deepak S.; Kundu, Gopal C.; Srivastava, Rohit; Selvaraj, Kaliaperumal (ACS Applied Bio Materials, 2019)
Selective tissue visualization and localized tumor regression without affecting the surrounding healthy tissues are critical concerns in cancer nanomedicine. Importantly, the complete wrapping of a flimsy matrix like liposome by multifunctional graphene oxide is an interesting engineering idea for nanomedicine design. Moreover, designing a safe and biodegradable nanohybrid with significant theranostic ability is a current need for targeted combined therapies. Here, we report a comprehensive result of in vivo tumor diagnosis and phototriggered tumor regression using a biodegradable red emissive nanotheranostic system, viz., graphene oxide flakes fortified liposome (GOF-Lipo), functionalized with folic acid (FA): GOF-Lipo-FA. Graphene oxide support enhances the stability of drug-loaded liposomes in an extracellular environment that prevents the premature release of loaded anticancer drug from the liposomal cavity. Promising outcomes of tumor regression (∼300 to 25 mm3) from organized cellular and animal studies are demonstrated in this work. These studies reveal superior biocompatibility, deep intracellular localization, 4T1 breast tumor diagnosis, and long time tumor binding ability of an injected emissive nanohybrid. Overall, a single dose of designed multifunctional systems demonstrates the best tumor regression.